2019
DOI: 10.6004/jadpro.2019.10.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Challenge of Immune-Related Adverse Events With Optimized Telephone Triage and Dedicated Oncology Acute Care

Abstract: Immune checkpoint inhibitors (ICIs) have improved outcomes for many patients with advanced cancers. However, managing the immune-related adverse events (irAEs) associated with these agents is challenging. Late recognition and/or inadequate irAE management can result in ICI discontinuation or termination, negatively impacting patient outcomes and increasing unplanned emergency department visits, hospital admissions, and costs of care. Improved clinician training and infrastructure development are needed to adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…An efficient follow-up process that facilitates the monitoring and reporting of irAEs in a timely manner is important for ensuring patient safety. Previous studies have shown that ePRO follow-up enables timely and continuous collection of information regarding symptoms in a cost-effective manner [9][10][11][12][13][14] and results in an improved QOL, fewer ED visits, longer duration of palliative chemotherapy, and superior quality-adjusted survival. 15,16 However, the efficacy of ePRO follow-up has not been examined in patients treated with…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An efficient follow-up process that facilitates the monitoring and reporting of irAEs in a timely manner is important for ensuring patient safety. Previous studies have shown that ePRO follow-up enables timely and continuous collection of information regarding symptoms in a cost-effective manner [9][10][11][12][13][14] and results in an improved QOL, fewer ED visits, longer duration of palliative chemotherapy, and superior quality-adjusted survival. 15,16 However, the efficacy of ePRO follow-up has not been examined in patients treated with…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of studies, especially large-scale randomized clinical trials, are limited. Hoffner and Rubin reported improvements in telephone triage by using immuno-oncology–essential materials to reduce the burden of irAE follow-up. Le et al evaluated the impact of a pharmacist-led irAE follow-up process that reduced the times required for physicians to manage irAEs and increased physician confidence.…”
Section: Introductionmentioning
confidence: 99%
“…While the high therapeutic efficacy of ICIs has been confirmed, serious immune-related adverse events (irAEs) have also been shown to occur [3,4]. irAEs are the side effect caused when this activated immune function is excessive, causing severe damage to various organs throughout the body [5][6][7][8][9]. However, this may contribute to favorable anti-tumor effects and a prolonged prognosis due to a strong immune response [10].…”
Section: Introductionmentioning
confidence: 99%
“…1 Data demonstrate that up to 40%-50% of patients receiving chemotherapy and 25% of patients receiving immunotherapy seek emergency care because of treatment-related side effects. 2 Acute hospital visits affect patient outcomes by delaying treatment, lessening quality of life, burdening caregivers, and increasing overall health care costs. Many emergency visits are avoidable with proper preventative management of key treatment-related conditions that are common causes of emergency visits in patients with cancer receiving antineoplastic therapy: anemia, dehydration, diarrhea, emesis, fever, nausea, neutropenia, pain, pneumonia, and sepsis.…”
Section: Introductionmentioning
confidence: 99%